The Trunk Line Rate System: A Distance Tariff - Ripley, William Z. (Quarterly Journal of Economics, 1906)
The Trunk Line Rate System: A Distance Tariff Get access William Z. Ripley William Z. Ripley Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 20, Issue 2, February 1906, Pages 183–210, https://doi.org/10.2307/1883652 Published: 01 February 1906